1997
DOI: 10.1111/j.1749-6632.1997.tb46178.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect Myosuppressins and Sulfakinins Stimulate Release of the Digestive Enzyme α‐Amylase in Two Invertebrates: The Scallop Pecten maximus and Insect Rhynchophorus ferrugineus

Abstract: The myosuppressins represent a subfamily of the insect FMRFamide-related peptides that share the common C-terminal heptapeptide sequence Asp-His-Val-Phe-Leu-Arg-Phe-NH,,' and have been identified in diverse insect species including the cockroach Leucophaea maderae, locusts Schistocerca gregaria and Locusta migratoria, the fleshfly Neobelleria bullata, and the fruitfly Drosophila melanogaster. Members of this family affect insect muscles, being potent inhibitors of cardiac and visceral muscle in addition to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 6 publications
3
45
0
Order By: Relevance
“…It is the belief of many that these structural similarities are the result of a common ancestry for the two groups of peptides (Nachman et al, 1986a;Nachman et al, 1986b;Nichols et al, 1988;Veenstra, 1989;Schoofs et al, 1990;Maestro et al, 2001;Torfs et al, 2001;Nachman et al, 2005). In addition to the observed sequence homologies, the hypothesis of a common ancestor for the CCK/gastrins and the sulfakinins is supported by the findings that both share a number of conserved functions: both groups are myoactive on the gut, induce the release of the enzyme amylase from the digestive system, and serve as satiety factors (Nachman et al, 1997;Wei et al, 2000;Maestro et al, 2001;Harashini et al, 2002;Downer et al, 2007). Moreover, studies of the effects of vertebrate CCK and of a partially purified CCK-like peptide in the spiny lobster showed that CCK itself can activate the neuronal pattern generators that control movements of the foregut in this species (Turrigiano and Selverston, 1989;Turrigiano and Selverston, 1990;Turrigiano et al, 1994).…”
Section: Do the Invertebrate Sulfakinins And The Vertebratementioning
confidence: 52%
See 1 more Smart Citation
“…It is the belief of many that these structural similarities are the result of a common ancestry for the two groups of peptides (Nachman et al, 1986a;Nachman et al, 1986b;Nichols et al, 1988;Veenstra, 1989;Schoofs et al, 1990;Maestro et al, 2001;Torfs et al, 2001;Nachman et al, 2005). In addition to the observed sequence homologies, the hypothesis of a common ancestor for the CCK/gastrins and the sulfakinins is supported by the findings that both share a number of conserved functions: both groups are myoactive on the gut, induce the release of the enzyme amylase from the digestive system, and serve as satiety factors (Nachman et al, 1997;Wei et al, 2000;Maestro et al, 2001;Harashini et al, 2002;Downer et al, 2007). Moreover, studies of the effects of vertebrate CCK and of a partially purified CCK-like peptide in the spiny lobster showed that CCK itself can activate the neuronal pattern generators that control movements of the foregut in this species (Turrigiano and Selverston, 1989;Turrigiano and Selverston, 1990;Turrigiano et al, 1994).…”
Section: Do the Invertebrate Sulfakinins And The Vertebratementioning
confidence: 52%
“…While not demonstrated directly, the distributions of sulfakinin-like immunoreactivity in many insects, particularly the dipterans, suggests a neuromodulatory role for this peptide family in the CNS (Duve et al, 1994;Davis et al, 1996;Nichols and Lim, 1996;East et al, 1997). Additionally, sulfakinins have been shown to stimulate the release of ␣-amylase from the midgut of both the weevil Rhynchophorus ferrugineus and the moth Opisina arenosella (Nachman et al, 1997;Harshini et al, 2002), and have been shown to be potent inhibitors of food intake in the locust Schistocerca gregaria, the cockroach Blatella germanica and the blowfly Phormia regina (Wei et al, 2000;Maestro et al, 2001;Downer et al, 2007).…”
Section: Sulfakinin Isoforms Appear Highly Conserved Both Within Andmentioning
confidence: 99%
“…Moreover, in B. germanica, mRNA expression levels of myosuppressin slightly decrease during maximum food intake . Myosuppressins also stimulate the release of the digestive enzyme -amylase in the red palm weevil (beetle), Rynchphorus ferrugineus (Nachman et al, 1997). Therefore, it appears that myosuppressin may play a role in digestion, acting as a neurotransmitter directly delivered to the hindgut and midgut tissue or locally released from endocrine-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…For gastrointestinal functions like muscular motility (Schoofs et al, 1993), salivary gland fluid secretion (Duve et al, 1992), midgut secretion of digestive enzymes (Fusé et al, 1999;Nachman et al, 1997), fluid secretion by Malpighian tubules (Beyenbach, 2003;Coast et al, 2002) and reabsorption by the hindgut (Coast et al, 2002), regulation by peptides is well documented. In contrast, to our knowledge only a single study was performed that is related to the regulation of midgut ion transport by neuropeptides (Lee et al, 1998).…”
Section: Effects Of Peptidesmentioning
confidence: 99%